KONSEKUENSI LOGIS PROFESIONALISME ADMINISTRASI GURU DALAM PENDIDIKAN ISLAM - Muhammad Ichsan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
As educators in schools, teachers have some duties and responsibilities not only to teach, but also to administer the school. Islam gives an overview of the duties and responsibilities for teachers in educational administration. The purpose of this paper is to propose a logical consequence of the professionalism of teachers in Islamic education. The professional duties of teachers as administrators in Islamic Education among others are to run instructional management and management in general such as managing school, utilizing the procedures and mechanisms to carry out their duties and act in accordance with the professional ethics. Besides, they also have to create a good physical condition of classrooms and qualified teaching tool, prepare for daily teaching, create conducive conditions so that learners have willingness to learn, design a lesson plan quarterly and annually, prepare for teaching in accordance with the schedule and lesson plan, evaluate and make a report of students’ achievement to several parties, make some revision based on the results of the evaluation, get to know the talents, interests and abilities of students, help students to improve and direct the talents and interests of students, participate and maintain reputation of the institution and write a report of teaching and learning activities. All in all, teachers also have a responsibility given by Allah to do their best in teaching.